EFFORTS TO IMPROVE STUDENTS' BEGINNING READING ABILITIES BY USING THE PHONICS METHOD IN CLASS II OF SDN PEJAMBEN I - Purnama Sari, Shelly; Azmi, Ulil (International Journal Multidisciplinary (IJMI), 2024)
Objective: This study addresses the issue of improving the learning outcomes of grade II students in Indonesian language subjects, specifically focusing on beginning reading through the phonics method. The aim is to enhance students' reading skills and overall academic performance in this area. Method: The research was conducted in two cycles, utilizing both quantitative and qualitative data collection methods. The data were analyzed to assess student learning outcomes, and consultations were made with established success criteria to measure progress. Observations during each cycle helped identify key areas for improvement, such as the need for clearer explanation of learning objectives, use of media, and fostering student engagement. Results: In the pre-cycle, several shortcomings were identified, such as the lack of a clear explanation of learning objectives, absence of media and props, and insufficient opportunities for students to express opinions. In Cycle 1, while improvements were made, there were still issues, such as the teacher's failure to encourage student participation. Cycle II showed further improvements, with better motivation and more engaging teaching methods. As a result, student learning outcomes improved significantly across both cycles. Novelty: This research demonstrates that the phonics method can effectively enhance the learning outcomes of grade II students in Indonesian language subjects related to beginning reading. The study highlights the importance of teacher engagement, the use of varied teaching strategies, and motivation in fostering better student performance.